Monitoring: Which institutions matter? - Chen, Xia; Harford, Jarrad; Li, Kai (Journal of Financial Economics, 2007)
Within a cost–benefit framework, we hypothesize that independent institutions with long-term investments will specialize in monitoring and influencing efforts rather than trading. Other institutions will not monitor. Using acquisition decisions to reveal monitoring, we show that only concentrated holdings by independent long-term institutions are related to post-merger performance. Further, the presence of these institutions makes withdrawal of bad bids more likely. These institutions make long-term portfolio adjustments rather than trading for short-term gain and only sell in advance of very bad outcomes. Examining total institutional holdings or even concentrated holdings by other types of institutions masks important variation in the subset of monitoring institutions.